Effect of Alkyl Side Chain Length on the Lithium-Ion Conductivity for Polyether Electrolytes - Sai, Ryansu; Hirata, Seiko; Tsutsumi, Hiromori; Katayama, Yu (Frontiers in Chemistry, 2022)
The design guidelines of polymer structure to effectively promote lithium-ion conduction within the polymer electrolytes (PEs) are crucial for its practical use. In this study, the electrolyte properties of a simple polyether having alkyl side chains with varied lengths (−(CH2)m−H, m = 1, 2, 4, 6, 8, and 12) were compared and established a valid design strategy based on the properties of the alkyl side chain. Various spectro-electrochemical measurements successfully connected the electrolyte properties and the alkyl side chain length. Steric hindrance of the alkyl side chain effectively suppressed the interaction between ether oxygen and lithium-ion (m ≥ 2), decreasing the glass transition temperature and the activation energy of lithium-ion transfer at the electrode-electrolyte interface. The strong hydrophobic interactions aligned and/or aggregated the extended alkyl group (m ≥ 8), creating a rapid lithium-ion transport pathway and enhancing lithium-ion conductivity. A clear trend was observed for the following three crucial factors determining bulk lithium-ion transport properties along with the extension of the alkyl side chain; (i) salt dissociability decreased due to non-polarity of the alkyl side chain, (ii) segmental mobility of polymer chains increased due to the internal plasticizing effect, and (iii) lithium-ion transference number increased due to the inhibition of the bulky anion transport by its steric hindrance. The highest lithium-ion conductivity was confirmed for the PEs with an alkyl side chain with moderate length (m = 4) at 70 °C, indicating the optimized balance between salt dissociability, polymer segmental mobility, and selective lithium-ion transfer. The length of an alkyl side chain thus can be a critical factor in improving the performance of PEs, including thermal stability and lithium-ion conductivity. Precise tuning of the alkyl side chain-related parameters such as steric hindrance, polarity, internal plasticizing effect, and self-alignment optimizes the polymer segmental mobility and salt dissociability, which is crucial for realizing high lithium-ion conductivity for PEs.